The importance of screening for serum free light chains in suspected cases of multiple myeloma and their impact on the kidney. (17th October 2014) - Talbot, B; Wright, D; Basnayake, K
Abstract : Multiple myeloma (MM) is the second most common haematological malignancy in the UK. We present a case series of three patients with light chain only myeloma who had normal serum protein electrophoretic studies at screening and were diagnosed using serum and urine free light chain assessment. This series reiterates the importance of thorough and robust screening for MM in patients presenting with renal disease. We review the up to date literature and we highlight the need to screen patients for MM with a combination of serum electrophoresis/immunofixation and either urinary or serum free light chain measurement and to maintain a high index of suspicion regardless of the presence or absence of proteinuria. We also discuss the emerging role of the serum free light chain assay.